2007
DOI: 10.4161/cc.6.9.4210
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Chromatin Patterns: An Instructive Mechanism for DNA Hypermethylation?

Abstract: Epigenetic gene silencing, and associated promoter CpG island DNA hypermethylation, is an alternative mechanism to mutations by which tumor suppressor genes may be inactivated within a cancer cell. These epigenetic changes are prevalent in all types of cancer, and their appearance may precede genetic changes in premalignant cells and foster the accumulation of additional genetic and epigenetic hits. These epigenetically modified genes constitute important categories of tumor suppressor genes including cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 45 publications
(73 reference statements)
6
92
0
Order By: Relevance
“…Moreover, it was recently demonstrated that precursor cancer SCs are plastic cell populations that can transition from epithelial to mesenchymal identity by regulating bivalent/monovalent marks on developmental genes. 40,41 The related aspects of the Lats2 À / À phenotype may not be coincidental, as one of the hallmarks of defective Hippo signaling is enhanced EMT. 42 Although Lats2 is best recognized for its role as a negative regulator of Yap in the Hippo pathway, our data strongly suggest that it is not solely in this capacity that Lats2 maintains the proper chromatin landscape and transcriptional performance of ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently demonstrated that precursor cancer SCs are plastic cell populations that can transition from epithelial to mesenchymal identity by regulating bivalent/monovalent marks on developmental genes. 40,41 The related aspects of the Lats2 À / À phenotype may not be coincidental, as one of the hallmarks of defective Hippo signaling is enhanced EMT. 42 Although Lats2 is best recognized for its role as a negative regulator of Yap in the Hippo pathway, our data strongly suggest that it is not solely in this capacity that Lats2 maintains the proper chromatin landscape and transcriptional performance of ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, H3K27 trimethylation is also an important component of 'bivalent' chromatin structures that are defined by the presence of both activating H3K4 trimethylation and repressive H3K27 trimethylation (Bernstein et al, 2006). Bivalent chromatin structures represent a defining molecular characteristic of embryonic stem cells and the relationship between H3K27 trimethylation, and de novo DNA methylation is assumed to reflect the presence of a stem cell-like epigenetic program in cancer cells (Ohm and Baylin, 2007). In agreement with this notion, a recent analysis also identified bivalent chromatin structures in human tumor samples (Aiden et al, 2010).…”
Section: Epigenetic Side Effects Of Global Dna Demethylationmentioning
confidence: 99%
“…There is compelling evidence, as we outlined earlier, showing that the PRC, which we have discussed as linked to abnormal gene silencing in cancer, target similar sets of CpG island-containing genes in ESC as in cancer [88,96,97]. A working hypothesis suggested vulnerability for these PcG-marked genes, which do not have promoter DNA methylation in ESC, to gain this change as stem/progenitor-like cells emerge during tumorigenesis [88,97,154] (Figure 1). This abnormal methylation may, then, help abnormally lock in activation of stem cell pathways and contribute to the self-renewing ability of cancer cell subpopulations.…”
Section: Epigenetics and Cancer Stem Cell Hypothesismentioning
confidence: 99%
“…A key hypothesis is that tumors are initiated through abnormal expansion of clonal stem/progenitor cells, which evolve in the setting of the chronic cell renewal events attendant to high-risk states for www.cell-research.com | Cell Research Hsing-Chen Tsai and Stephen B Baylin 507 npg cancer, such as chronic inflammation. Here, in concert, genetic and epigenetic changes may help provide the survival advantage which allows these cell subpopulations to withstand the toxic environment of inflammation constituted by accumulating reactive oxygen species, and which then contributes to tumor initiation and progression [154,155] (Figure 1). Studies on epigenetic alterations both in stem cells and in cancer are providing important insights into the stem/progenitor cell origin of cancer [154].…”
Section: Epigenetics and Cancer Stem Cell Hypothesismentioning
confidence: 99%
See 1 more Smart Citation